Misophonia impact questionnaire (MIQ), tinnitus impact questionnaire (TIQ), and hyperacusis impact questionnaire (HIQ): Factor analysis, test-retest reliability, and minimum detectable change using a non-clinical population - Hashir Aazh; Fatma Betul Kula (PLoS ONE, 2025)
The objectives of this study were to (1) assess if previously reported unidimensional factor structure of the Misophonia Impact Questionnaire (MIQ), Tinnitus Impact Questionnaire (TIQ), and Hyperacusis Impact Questionnaire (HIQ) can be confirmed in a nonclinical population, and (2) examine test-retest reliability and establish the minimum detectable change (MDC) for MIQ, TIQ and HIQ. 451 people completed the MIQ and HIQ sections of an online survey. A sub-sample of 173/451 who had tinnitus completed the TIQ too. 130/451 participants completed the second survey with 2 weeks interval for the MIQ and HIQ and 32/173 participants with tinnitus completed the TIQ in the second survey. All questionnaires showed excellent internal consistency, with Cronbach’s α of 0.93 for both the MIQ and TIQ and 0.91 for the HIQ. Confirmatory factor analysis (CFA) showed that the MIQ, TIQ and HIQ were all one-factor questionnaires. Based on the intra-class correlation coefficients (ICC) values, the test-retest reliability was good for MIQ and HIQ and it was excellent for TIQ. Based on the MDC values, when these questionnaires are used for repeated measurements, the minimum amount of change that constitutes a true change is ≥ 8 for the total score of MIQ, ≥ 4 for the TIQ, and ≥ 7 for the total score of HIQ. In conclusion, the MIQ, TIQ and HIQ can be used in clinical practice or research setting to measure the impact of misophonia, tinnitus and hyperacusis on the individual’s life, respectively, as one-factor questionnaires with excellent internal consistency and good to excellent test-retest reliability.